Prehistoric art as prehistoric culture : studies in honour of Professor Rodrigo de Balbín-Behrmann - Bueno Ramírez, Primitiva,; Bahn, Paul G.,; Balbín Behrmann, R. de (Archaeopress archaeology., 2015)
Professor Rodrigo de Balbín has played a major role in advancing our knowledge of Palaeolithic art, and the occasion of his retirement provides an excellent opportunity to assess the value of prehistoric art studies as a factor in the study of the culture of those human groups which produced this imagery. The diverse papers in this volume, published in Professor de Balbín's honour, cover a wide variety of the decorated caves which traditionally defined Palaeolithic art, as well as the open-air art of the period, a subject in which he has done pioneering work at Siega Verde and elsewhere. The result is a new and more realistic assessment of the social and symbolic framework of human groups from 40,000 BP onwards.